Leadership Style And Leadership Effectiveness: Moderating Role Of National Culture Dimensions - Kheireddine, Adib Ali (2008)
In the current era of globalization, cross-cultural business interactions are becoming the norm rather than the exception, involving not only managers, employees and colleagues, but also customers, suppliers and business partners. With this, today's leaders of multinational companies (MNC) are required to have international skills and awareness (Derr, Roussillon, and Bournois, 2002) and the success of MNC depends on the effective leadership and how well the leader acts in a manner sensitive to the national culture in which they operate (Prieto, 2004). Hence current leaders in MNC are challenged to have leadership robust in cross-cultural environment. Per Bass ( 1997) Transformational (TF) and transactional (TS) leadership have universality effects in all parts of the globe and in all forms of organizations but there are contradicting findings found (i.e. Pillai, Scandura, and Williams, 1999; Dubinsky, Yammarion, and Jolson, 1995).